Preparation and application of flexible force-induced luminescence intelligent sensing thin film device
By doping strontium aluminate-based electroluminescent powder with epoxy resin matrix and curing agent, flexible electroluminescent intelligent sensing film devices are solved, and the problem of difficult large-area and non-contact monitoring of existing structural health monitoring methods is achieved, and distributed contactless monitoring is achieved, reducing costs and improving monitoring accuracy.
Patent Information
- Application Number
- CN202510077929.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
The existing structural health monitoring methods have limitations, making it difficult to perform large-area, non-contact micro cracks and structural damage perceptions, and the sensor costs are high.
Flexible electroluminescent intelligent sensing film devices are prepared by doping strontium aluminate-based electroluminescent powder with epoxy resin matrix and curing agent. Uniform and multi-gate sensor devices are prepared through coating and 3D printing technology to achieve distributed contactless monitoring.
Distributed contactless monitoring of various engineering stress and strain distributions is realized, reducing sensor costs and improving monitoring accuracy and coverage.
Smart Images

Figure CN119798740A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical sensing technology, and mainly to a flexible mechanoluminescent intelligent sensing thin film device prepared by utilizing the mechano-optical properties of mechanoluminescent materials. Background Art
[0002] In today's engineering practice, although traditional structural health monitoring methods can evaluate the health of structures to a certain extent, they often have their limitations, such as only point or line measurements, high sensor costs, reliance on contact measurements, troublesome sensor deployment, and difficulty in sensing tiny cracks and structural damage. Mechanoluminescence (ML) refers to the phenomenon that materials convert mechanical energy into light energy when subjected to mechanical stimulation (such as pressure, impact, etc.), thereby achieving luminescence. Due to the unique force-light properties of mechanoluminescent materials, mechanical stimulation can be directly converted into light signals without external energy supply. Therefore, they have the potential to be used as sensors, and can achieve non-contact measurement monitoring and large-area measurement. They show great potential and research prospects in structural health monitoring, intelligent sensing, biomedicine, smart wearables, etc. However, how to make mechanoluminescent materials into suitable sensor devices, how to reconstruct stress distribution through luminescent images, how to determine the force direction through luminescent images, and how to better apply them to actual engineering monitoring and applications have become urgent problems to be solved. Summary of the invention
[0003] The present invention provides a flexible mechanoluminescent intelligent sensing thin film device, which can perform distributed contactless monitoring of various engineering stresses and strain distributions.
[0004] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions:
[0005] The present invention provides a preparation and application of a flexible mechanoluminescent intelligent sensing thin film device, comprising the following steps:
[0006] 1. A strontium aluminate-based mesoluminescent powder is mixed with an epoxy resin matrix and a curing agent in different proportions to obtain a strontium aluminate / epoxy resin composite material. Preferably, the mesoluminescent powder is mixed with the epoxy resin matrix and the curing agent in a ratio of 1:0.5 to 5.
[0007] 2. The composite material is uniformly coated and cured by a film applicator, and then processed and cut to be used as a uniformly distributed flexible mechanoluminescent intelligent sensing thin film device in the fields of structural health monitoring, component crack expansion, and component stress analysis.
[0008] Preferably, the thickness of the uniformly distributed flexible mechanoluminescent intelligent sensing thin film device is 100 to 300 microns.
[0009] 3. The present invention also provides the use of the above-mentioned composite material body as 3D printing slurry after preliminary pre-curing, and forming a flexible sensor device through 3D printing, and its application in the fields of structural health monitoring, component crack propagation, and component stress analysis.
[0010] 4. The present invention also provides a method for reconstructing stress field distribution using mesoluminescence images, using mesoluminescence images and finite element simulation images to find corresponding relationships, and using the corresponding relationships to reconstruct stress field distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 For various flexible mechanoluminescent intelligent sensing thin film devices;
[0012] Figure 2 Microscopic characterization of flexible mechanoluminescent smart sensing thin film devices;
[0013] Figure 3 The relationship curve between ML intensity and strain of uniformly distributed flexible mechanoluminescent intelligent sensing thin film device
[0014] Figure 4 To determine the direction of force using 3D printed multi-gate flexible mechanoluminescent intelligent sensing thin film devices
[0015] Figure 5 Obtain the surface mechanoluminescence image of the component and the comparison diagram of finite element simulation and stress field reconstruction diagram for the uniformly distributed flexible mechanoluminescent intelligent sensing thin film device
[0016] Figure 6 Uniformly distributed flexible mechanoluminescent intelligent sensing thin film device to monitor the cracks in concrete samples DETAILED DESCRIPTION
[0017] The present invention provides a method for preparing a strontium aluminate-based multi-component rare earth doped mechanoluminescent powder, comprising the following synthesis steps:
[0018] Aluminum oxide, strontium carbonate, europium oxide, dysprosium oxide, neodymium oxide, and boric acid are weighed in corresponding molar ratios and then mixed evenly to obtain a calcined powder precursor;
[0019] calcining the powder precursor at high temperature to obtain the strontium aluminate-based multi-component rare earth doped mesoluminescent powder;
[0020] In the present invention, unless otherwise specified, all raw materials used are commercially available products.
[0021] In the present invention, a method for preparing a flexible mechanoluminescent intelligent sensing thin film device is provided. The mechanoluminescent powder prepared above is mixed with AB type epoxy resin glue in different proportions as a precursor slurry. Various forms of mechanoluminescent flexible sensor devices, such as uniformly distributed and 3D printed gate films, can be prepared by coating and 3D printing.
[0022] The epoxy resin described in the present invention is a commercially available highly transparent AB type epoxy resin, the main components of which are epoxy resin and a transparent defoamer.
[0023] The present invention provides a method for monitoring component stress distribution and reconstructing stress field by using a flexible mechanoluminescent intelligent sensing thin film device.
[0024] The following is a clear and complete description of the technical solution of the flexible mechanoluminescent smart sensing thin film device described in the present invention in combination with examples. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] Preparation of SrAl2O4:1%Eu-doped SrAl2O4-based multi-element rare earth-doped electroluminescent powder by high temperature solid phase reaction 2+ ,1%Dy 3+ ,1%Nd 3+ ,(SAOEDN), includes the following steps:
[0027] Step 1: Weigh 0.1 mol Al2O3, 0.1 mol SrCO3, 0.1 mol Al2O3, 0.0005 mol Eu2O3, 0.0005 mol Dy2O3, 0.0005 mol Nd2O3, and 0.01 mol H3BO3 according to the chemical atomic stoichiometric ratio, mix the raw materials, put them into a beaker, add a magnetic rotor and an appropriate amount of ethanol, and stir on a magnetic stirrer for 2 hours.
[0028] Step 2: Transfer the mixture to a zirconia ball mill. The ball mill beads in the ball mill are set at a mass ratio of 1:1 to the powder sample. The ball mill beads are graded according to the principle of equal surface area. The fully ground suspension is placed in a drying oven to dry the ethanol to obtain a uniformly dispersed precursor powder, and the precursor powder is transferred to a corundum crucible.
[0029] Step 3: Transfer the raw material powder to a hydrogen furnace and calcine the sample at 1400°C for 4 hours in a mixed reducing atmosphere of 95% nitrogen and 5% hydrogen.
[0030] Step 4: Cool naturally, use ethanol as a dispersant for the calcined powder, ball-mill it again and dry it to remove the ethanol, and then use an ultrasonic vibration sieving instrument to sieve the powder to obtain mechanoluminescent powders of different particle sizes.
[0031] Example 2
[0032] Preparation of uniformly distributed flexible mechanoluminescent intelligent sensing thin film devices
[0033] Step 1: Weigh a certain amount of the SAOEDN mechanoluminescent powder and epoxy resin matrix material prepared in Example 1 according to a mass ratio of 1:2 and preliminarily mix the two.
[0034] Step 2: Further use ball milling to disperse the powder more evenly in the epoxy resin matrix material.
[0035] Step 3: Add a curing agent to the uniformly mixed slurry and stir thoroughly to obtain a uniformly dispersed precursor slurry.
[0036] Step 4: Evenly apply the precursor slurry on the surface of the release film, place it horizontally and wait for the slurry to solidify. After solidification, peel it off from the release film to obtain a uniformly distributed flexible mechanoluminescent smart sensing thin film device.
[0037] Example 3
[0038] Preparation of 3D printed multi-gate flexible mechanoluminescent smart sensing thin film devices
[0039] Step 1: The uniformly dispersed precursor slurry obtained in step 3 of Example 1 is loaded into a syringe and allowed to stand for 4 hours to pre-coagulate the slurry, thereby obtaining a slurry having rheological properties suitable for 3D printing.
[0040] Step 2: Use a 3D printing device to print the above slurry on release paper into a pre-designed multi-gate grid, place it horizontally, and peel it off after the slurry solidifies to obtain a 3D printed multi-gate flexible mechanoluminescent smart sensing thin film device.
[0041] Figure 1 The morphology of the flexible mechanoluminescent smart sensing thin film device under ultraviolet light is shown, and the flexible mechanoluminescent smart sensing thin film device is characterized by SEM, such as Figure 2 As shown, the device surface is smooth and complete, the epoxy resin and the mesoluminescent powder are tightly bonded, and the powder particles are evenly distributed in the epoxy resin. This lays the foundation for the effective operation of the device, ensures that the mechanical action can be transmitted smoothly, and ensures the excellent optical and mechanical properties of the device.
[0042] The mechanical properties of the flexible mechanoluminescent smart sensing thin film device were tested to evaluate its ML characteristics. The uniformly distributed flexible mechanoluminescent smart sensing thin film device was cut into strips with appropriate length and width of 1 cm. The two ends of the strip film were respectively adhered to two metal sheets, and the length of the unadhered part in the middle was 1 cm, that is, a 1 cm × 1 cm stretching area was reserved in the middle. The metal sheet was then fixed on a universal testing machine with a clamp for stretching, and the luminescent image was recorded with a camera. The relationship curve between the ML strength and strain of the uniformly distributed flexible mechanoluminescent smart sensing thin film device was obtained (see Figure 2). Figure 3 The results show that the ML intensity of the flexible mechanoluminescent smart sensing thin film device increases linearly with the strain size, indicating the great application potential of the above-mentioned thin film device in sensing monitoring.
[0043] At the same time, in the uniaxial compression test of cubic specimens using 3D printed multi-gate flexible mechanoluminescent intelligent sensing thin film devices, the changes between the various gates can qualitatively determine the direction of force, such as Figure 4 As shown, the places where the stripes are close together are under compression, and the places where the stripes are far apart are under tension, which can assist in force identification.
[0044] Example 4
[0045] Monitoring and verification of epoxy resin block stress deformation using flexible mechanoluminescent intelligent sensing thin film devices
[0046] Step 1: Epoxy resin is a commonly used engineering material. The uniformly distributed flexible mechanoluminescent intelligent sensing thin film device film prepared in Example 2 is cut into a suitable shape and pasted on an epoxy resin cylindrical block using the same epoxy resin-based adhesive to ensure that the bonding layer matches the film. The size of the epoxy resin block is 20 mm in diameter and 15 mm thick.
[0047] Step 2: Use a universal testing machine to load the epoxy resin block with the flexible force-induced luminescent intelligent sensing thin film device pasted thereon at a loading speed of 2 mm / min, and use a camera to observe the changes in the force-induced luminescent image to obtain the force-induced luminescent image.
[0048] Step 3: The finite element analysis software Abaqus was used to perform finite element simulation on the compression process of the cylinder. The model size parameters were consistent with the actual object. The model constitutive parameters were: Young's modulus was 3000MPa, Poisson's ratio was 0.38, and a load was applied to it through a constant displacement in the vertical direction to obtain the surface stress cloud map of the finite element simulated uniaxial compression.
[0049] By comparing the simulation results with the luminescent images produced by the actual flexible mechanoluminescent intelligent sensing thin film device, it can be found that the two have extremely high similarity, indicating that the flexible mechanoluminescent intelligent sensing thin film device has the ability to monitor material deformation and force.
[0050] In order to reconstruct the stress field on the actual component surface, a data extraction line is drawn from the center of the component to the edge on the component ML cloud map and stress cloud map. The angle between the line segment and the vertical direction is, and the distance between the point on the line and the center of the circle is a. The gray value is extracted along the straight line on the ML cloud map as the ML intensity, and the simulated stress result is extracted along the straight line on the simulated stress cloud map. The data extracted on the line segment is normalized to 45°, and the corresponding relationship between the ML intensity and the simulated stress result is established. Then, the ML intensity field is calibrated using the corresponding relationship, thereby reconstructing the stress field on the component surface, as shown in FIG. Figure 5 Shown
[0051] Example 5
[0052] Monitoring the development of cracks in concrete specimens using uniformly distributed mechanoluminescent flexible sensors
[0053] Concrete is one of the most common materials in actual engineering. The cracks generated in various concrete components during their service are extremely important. The precursor of concrete damage is often the development of concrete cracks. Therefore, it is necessary to develop monitoring methods that can detect the development of concrete cracks in real time.
[0054] Step 1: Cut the uniformly distributed mechanoluminescent flexible sensor device film prepared in Example 2 into a suitable shape, and use the same epoxy resin-based adhesive to stick it on the epoxy resin cylindrical block to ensure that the bonding layer and the film match. The size of the concrete block is a cube with each side length of 5 cm.
[0055] Step 2: Similar to Example 4, a vertical load is applied to the concrete block using a universal testing machine and a camera is used to observe the development of the cracks to obtain a luminescent image of the crack development.
[0056] Figure 6The image of using uniformly distributed force-induced luminescence flexible sensor to monitor the development of concrete sample cracks is shown. The following characteristics can be seen from the image: the distribution of the highlight part is random, and it is often distributed vertically at a certain inclination angle, and it is distributed along an arc at the edge of the component; the highlight part is not a straight line but an irregular curve with some branches. These characteristics also reflect the characteristics of concrete crack expansion and distribution: during the compression process, concrete is compressed vertically and stretched horizontally, so concrete will produce vertical cracks, and the cracks will gradually increase in the horizontal direction; in addition, since concrete is a multi-phase inhomogeneous material, the initiation and expansion of its cracks are somewhat random, and when the crack encounters aggregates or other defects during the expansion process, branch cracks will be generated. Different branch cracks will meet and merge inside the material to produce larger cracks, so the cracks show randomness and branch morphology. This shows that the force-induced luminescence flexible sensor can effectively sense the expansion of the main cracks on the concrete surface. This further verifies the applicability and reliability of the force-induced luminescence flexible sensor in concrete components.
Claims
1. Preparation and application of a flexible mechanoluminescent intelligent sensing thin film device, characterized in that: The following steps are involved: The mechanoluminescent powder and AB type epoxy resin glue are mixed in different proportions and stirred evenly to obtain a precursor slurry; The above-mentioned precursor slurry can be used to prepare different forms of mechanoluminescent flexible sensor devices, such as uniformly distributed and 3D printed gate flexible mechanoluminescent intelligent sensing thin film devices.
2. The preparation method according to claim 1, characterized in that: The precursor slurry is evenly coated on the surface of the release film by using a coater, and after being horizontally left to solidify, it is peeled off from the release film to obtain a uniformly distributed flexible mechanoluminescent intelligent sensing thin film device.
3. The preparation method according to claim 1, characterized in that: The slurry is printed into a pre-designed multi-gate grid on release paper using a 3D printing device, and after being horizontally left to solidify, it is peeled off to obtain a 3D printed multi-gate flexible mechanoluminescent intelligent sensing thin film device.
4. The method for preparing the flexible mechanoluminescent intelligent sensing thin film device according to claim 1, characterized in that: The mesoluminescent powder is rare earth doped strontium aluminate mesoluminescent powder SrAl2O4:Eu 2+ ,Dy 3+ ,Nd 3+ , (SAOEDN).
5. The method for preparing the flexible mechanoluminescent intelligent sensing thin film device according to claim 1, characterized in that: The mass ratio of the mechanoluminescent powder to the AB type epoxy resin is 1:0.5-5.
6. The method for preparing the flexible mechanoluminescent intelligent sensing thin film device according to claim 2, characterized in that: The thickness of the uniformly distributed flexible mechanoluminescent intelligent sensing thin film device can be adjusted by a film coater, and the thickness is 100 to 300 microns.
7. A flexible mechanoluminescent intelligent sensing thin film device prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Flexible mechanoluminescence optical fiber, preparation method thereof and large-strain sensing application device
CN112213815A
Preparation method of pavement epoxy coating with mechanoluminescence performance
CN115572520A
Photo-curing 3D printed mechanoluminescent ceramic as well as preparation method and application thereof
CN115925421A
Stress luminescent material powder and resin composition
JP2017149844A
Mechanoluminescence paint sensor for stress and crack visualizations
US20160216211A1